Óxidos mistos a base de lantânio e zircônio com dopagem de ferro ou níquel: características estruturais e remoção de corantes têxteis - Firmino, Valber Eduardo Silva (2023)
Mixed oxides are studied for several applications, among them those that can deal with catalysis or adsorption phenomena. In this work, the effect of the synthesis route and the effect of the dopant metal to obtain mixed oxides of pyrochlore structure with theoretical composition La2,0Zr2,0O7 and La2,0M0,3Zr1,7O7 (M = Ni or Fe) on the formation of the phase and removal efficiency of Congo red textile dye. The materials were synthesized by the modified protein method using collagen as a chelating agent, heat treated at 350 °C and subjected to calcination at 900 °C. The materials were characterized by Fourier transform infrared spectrophotometry (FTIR), thermogravimetry (TG), X-ray diffraction (XRD) by the powder method, scanning electron microscopy (SEM), N2 adsorption at 77K and point of zero charge (PZC). The results obtained indicated the formation of the pyrochlore phase in the three materials, with formation of secondary phases in the doped materials. The FTIR spectra showed differences between the heat-treated and calcined materials, especially regarding the metal-oxygen bond (M-O). The method proved to be quite effective in forming the desired phase, obtaining materials with high surface area and smaller crystallite size compared to other methods. The obtained materials were submitted to Congo red dye adsorption studies. The LZO material proved to be efficient in the adsorption process with Emax = 93%. The studies referring to the contact time and analysis temperature showed that as the temperature increases, the adsorption efficiency decreases. The experimental data were applied to kinetic models of pseudo first order, pseudo second order and variable constants. The materials were submitted to the study of reuse in cycles maintaining high removal efficiency. The adsorbents obtained were also submitted to industrial effluent removal tests and compared with silica gel and activated carbon materials, presenting results similar to those of industrially known materials. It was proven that the pyrochlore structure remained after the adsorption studies, which indicates stability and the possibility of reuse.